Portrait of Samuel P. Massie (1987)
Black and white photographic portrait of Samuel P. Massie (1919-2005). Massie was an African American chemist who researched the synthesis and development of therapeutic drugs, focusing on treating malaria, herpes, meningitis, and gonorrhea. In 1966 he became the first African American professor at the U.S. Naval Academy.
Keywords: African American chemists; Portraits; Massie, Samuel; Chemists